EFFECT OF OVERLOADED VEHICLES ON VEHICLE DAMAGE FACTOR AND PAVEMENT REHABILITATION (FSTPT Indonesia, 2023)
Overloading has become a common problem, especially in developing countries including Indonesia. Overloaded vehicle has negative impacts on the pavement, one of which is premature deterioration which leads to increased rehabilitation costs. This research was conducted to calculate the impact of overloaded vehicles on the pavement in terms of vehicle damage factor (VDF), ESAL, and rehabilitation costs based on the traffic data on Jakarta-Cikampek Toll Road. The calculation is done using three scenarios to compare different conditions. Scenario 1 is the actual condition of the traffic. Scenario 2 is the ideal condition where the axle configuration of the overloaded vehicles was changed to accommodate the load. Scenario 3 is the ideal condition where the excess overload is carried by adding more vehicles. It was found that by changing the vehicles' axle configuration, the rehabilitation cost was reduced as much as 70.12%, while adding more vehicles reduced the cost by 55.14%. ABSTRAK Overloading sudah menjadi masalah umum, terutama di negara berkembang termasuk Indonesia. Kendaraan yang kelebihan muatan memberikan dampak negatif terhadap perkerasan, salah satunya adalah kerusakan dini yang berujung pada peningkatan biaya rehabilitasi. Penelitian ini dilakukan untuk menghitung dampak kelebihan beban kendaraan pada perkerasan ditinjau dari daya rusak jalan atau vehicle damage factor (VDF), ESAL, dan biaya rehabilitasi berdasarkan data lalu lintas di Jalan Tol Jakarta-Cikampek. Perhitungan dilakukan dengan menggunakan tiga skenario untuk membandingkan kondisi yang berbeda. Skenario 1 adalah kondisi lalu lintas yang sebenarnya. Skenario 2 adalah kondisi ideal dimana konfigurasi sumbu dari kendaraan yang kelebihan beban diubah agar dapat mengangkut beban tanpa overloading. Skenario 3 adalah kondisi ideal dimana beban berlebih diangkut dengan menambah jumlah kendaraan. Ditemukan bahwa dengan mengubah jumlah gandar kendaraan, biaya rehabilitasi berkurang sebanyak 70,12%, sementara menambah jumlah kendaraan mengurangi biaya rehabilitasi sebesar 55,14%.